Smart grid: evaluation and trend in Brazil - Silva, Ricardo Moreira da (2014)
The Smart Grid is considered the most promising conglomerate of technology to be applied for the improvement and optimization of all power production in electrical engineer. Smart Grid's concept is being more and more recognized for its importance for representing a way to meliorate the energetic efficiency of the electric system, reducing consumption, allowing intensive use of energy generation renewable sources. Therefore, the goal of this article is to explore and present Smart Grid's concepts and its global evolution, so as perform an assessment on Smart Grid's tendencies in Brazil. In order to do this, we shown the concepts of Smart Grid, its benefits and impacts in the electric system's value chain, the barriers to its diffusion in Brazil and the paths of investments' incentives for deployment of the new technology. Accordingly, we reach the conclusion that the researches point to a long and challenging trajectory for the development and implantation of Smart Grid's technology in Brazil, which is still in a embryonic phase of pilot projects for the knowledge and technology development implantation.